Perfil das demandas judiciais no período de 2008 - 2018 - COSTA, Edenira Nunes (Universidade Federal do Oeste do Pará, 2024)
In Brazil, the State assumes the responsibility of guaranteeing the health of the population, making it a fundamental right. Through the 1988 Constitution, citizens' access to power was also expanded, with the opening of the Judiciary to individual and collective demands, enabling a scenario favorable to the so-called "judicialization phenomenon". This paper analyzes the process of judicialization in Brazil, based on the judicial demands in the period 2008-2018, which used the Virtual Health Library as a data source to select articles from the LILACS and MEDLINE database. Health with the main subjects: Right to health, Pharmaceutical assistance, Unified Health System and Access to Health services. Together with quantitative data analysis related to the processes of judicialization sent to the State Secretariats of the Brazilian states requested through the Citizen Information System. In Brazil, from 2008 to 2018, only five (5) publications portray the judicial process through quantitative data, which are related to hospital / outpatient services and refer to rare diseases. Analyzing the data obtained from the states, it was possible to observe the presence of a large number of legal demands for low-cost drug applications, regulated for dispensing in the primary network of the public network, showing that the lists of RENAME and REMUNE's essential medicines are not yet available prescribers in the Unified Health System; The research shows that the states do not yet have a standard system for systematizing data on the number of lawsuits, presenting heterogeneity in data storage, making data collection and analysis impossible, resulting in a lack of control and evaluation when dealing with how much judicial demands are jeopardizing the operation of the health network, because when referring to compliance with judicial decisions, States have financial resources not initially planned. This study shows the need for studies regarding the judicial demands in the Public Health System detailing the aspects that led the user to turn to the judiciary to have access to the health service and what actions within the organization, management planning have been taken to reduce judicial demands, in order to guarantee health in an equitable way for SUS users.